2017
DOI: 10.3390/w9110894
|View full text |Cite
|
Sign up to set email alerts
|

Contamination Event Detection Method Using Multi-Stations Temporal-Spatial Information Based on Bayesian Network in Water Distribution Systems

Abstract: Abstract:As a core part of protecting water quality safety in water distribution systems, contamination event detection requires high accuracy. Previously, temporal analysis-based methods for single sensor stations have shown limited performance as they fail to consider spatial information. Besides, abundant historical data from multiple stations are still underexploited in causal relationship modelling. In this paper, a contamination event detection method is proposed, in which both temporal and spatial infor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…The proposed model outperformed benchmark models, and the results showed that the detection capacity significantly improved. Yu et al [2] proposed a method for detecting water pollution using multi-station spatial and temporal data. WDS consists of multiple stations with large-scale characteristics and high complexity.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…The proposed model outperformed benchmark models, and the results showed that the detection capacity significantly improved. Yu et al [2] proposed a method for detecting water pollution using multi-station spatial and temporal data. WDS consists of multiple stations with large-scale characteristics and high complexity.…”
Section: Related Workmentioning
confidence: 99%
“…Water distribution systems (WDS) are vital to cities' water supply, particularly given that their safety directly affects public health. However, the water quality is hard to maintain in WDS due to the effects of the distance and time taken during the long process of delivery from the water source to the end-users [2]. Besides, typically major parts of WDS exist in the open environment; thus, it is vulnerable to external disturbances, such as sabotage.…”
Section: Introductionmentioning
confidence: 99%
“…Multi‐information fusion (MIF) is a consensus‐based decision support technique, which provides cross‐validated decisions that are reliable to deal with non‐uniqueness in PSD (Dickerson et al., 2007; Kazai et al., 2013; Yu et al., 2017). This study aims to utilize MIF to make full use of the difference between the diffusion coefficient and the attenuation coefficient of COD Mn , NH 3 ‐N, and Total‐P indicators for cross‐validation (Perelman et al., 2012).…”
Section: Introductionmentioning
confidence: 99%